S. mansoni Trapping in Lungs Contributes to Resistance to Reinfection - Knopf, Paul Mark; Suri, Parmjeet Behl (Frontiers in Immunology, 2015)
Paul and Pammi's combined research career of 60 plus years focused on preventive vaccine against schistosomiasis. Worm migration studies in rats using 75SE-methionine labeled cercariae and analyzed by autoradiography demonstrated that resistance to reinfection (R/R) requires host immune response resulting in worm death. In permissive hosts, anti eggs immunity causes inflammation leading to host death, whereas in non-permissive hosts this is not the case due to reduced egg burdens. Pathology caused by the presence of eggs & inflammatory debris due to immune attack on worms is important for vaccine design! Protective immune responses are perhaps induced when naïve hosts are vaccinated with either schistosome-derived molecules or attenuated cercariae as suggested by the induction of protective anti-parasite antibodies and monoclonal antibodies. Others and we have used such findings of successful immunizations with schistosome-derived molecules and evidence of R/R in primary hosts as the criteria for embarking on a research career to develop anti schistosome vaccine. However, these immunological strategies rarely produce 85-90% R/R as is achievable by portal-caval shunting. Alternatively induction of anti-schistosoma immunity induces portacaval shunting? However, this has not been tested but seems highly unlikely. Pammi identified a tegumental glycoprotein Sm25 as a candidate vaccine antigen. Differential screening with sera from twice-infected rats, protective (F2x) from Fisher vs.non protective (W2x) from Wistar Furth rats was used and corresponding gene (GP22) cloned. Codons 43-182 amplified by PCR and cloned in pET 15b bacterial expression system. Recombinant protein r140, in combination with different adjuvants was tested for its vaccination potential in mice. Despite high titre anti-r140 antibodies with protective isotypes that detected a 25kDa surface antigen, no protection against subsequent cercarial challenge nor any effect on liver eggs yield was observed.